The use of the laser confocal scanning microscopy to measure resin remnants on customized lingual bracket - Can Kuskonmaz; Alberto De Stefani; Gilberto Artioli; Matteo Zanarini; Giulio Alessandri Bonetti; Giovanni Bruno; Antonio Gracco (BMC, 2020)
Abstract Background The study aimed to evaluate the permanence of resin and enamel remains on lingual brackets at the end of orthodontic treatment and after the debonding procedure. The evaluation of resin remnants on customized lingual brackets bases has never done before in other studies because they are curved, and traditional techniques are not applicable. Methods The sample consisted of 100 lingual brackets (25 incisors, 25 canines, 25 premolars, 25 molars) scanned with a confocal laser microscope (OLS4000). We measured the brackets' surface and the area of resin remnants with the software of the microscope. Median and quartiles were presented to describe the data. ARI calculation was indirect for each tooth, measuring the resin remnants to the total surface of the bracket. The Kruskal-Wallis test and Fisher test were applied respectively to compare the percentages of remnants and the frequencies of the ARI between the four groups. Results After the analyses, 13 brackets had no adhesive remnants (ARI 0), 29 brackets had less than 50% of resin remnants (ARI 1), 50 brackets had more than 50% of resin remnants (ARI 2), and 8 brackets had 100% of adhesive (ARI 3). Canines brackets presented the lower amount of resin followed by premolars, incisors, and molars. Conclusion Lingual brackets showed a high frequency of ARI = 2. The median percentage of the bracket surface covered by resin was 41%. We observed a slight tendency of more resin remnants on molar brackets, due to half-pad configuration. The authors suggest paying attention during the debonding procedure of molar brackets since a stronger connection between the adhesive and the bracket mesh means a higher risk of enamel damage.